2016
DOI: 10.1108/intr-09-2015-0272
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an instrument to measure online retailing ethics

Abstract: Emerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series volumes, as well as providing an extensive range of online products and additional customer resources and services. Emerald is both COUNTER 4 and TRANSFER compliant. The organization is a partner of the Committee on Publication Ethics (COPE) and also works with Portico and the LOCKSS initiative for digital archive preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 108 publications
4
62
0
8
Order By: Relevance
“…These especially concern "an attempt to deal with consumers in a secure, confidential, fair and honest manner that ultimately protects consumer's interests" (Roman 2007, p. 134). Researchers have concluded that ethical perceptions of the consumers' in online environment are a multidimensional construct consisting of various dimensions-such as privacy, security, fulfillment/reliability and non-deception (e.g., Roman 2007), service recovery (Agag 2016;Cheng et al 2014) and shared value (e.g., Agag 2016). However, to the best knowledge of the authors of this study, no research has examined consumers' ethical perceptions in the context of SEPs.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…These especially concern "an attempt to deal with consumers in a secure, confidential, fair and honest manner that ultimately protects consumer's interests" (Roman 2007, p. 134). Researchers have concluded that ethical perceptions of the consumers' in online environment are a multidimensional construct consisting of various dimensions-such as privacy, security, fulfillment/reliability and non-deception (e.g., Roman 2007), service recovery (Agag 2016;Cheng et al 2014) and shared value (e.g., Agag 2016). However, to the best knowledge of the authors of this study, no research has examined consumers' ethical perceptions in the context of SEPs.…”
Section: Introductionmentioning
confidence: 86%
“…This model should include the embedded role of consumer participation and the co-creation of value on online platforms. Previous e-commerce research recognizes both antecedents to ethical perceptions, such as consumers' Internet expertise (Roman and Cuestas 2008) and the consequences of ethical perceptions such as relationship quality (Agag 2019), word-of-mouth (Roman and Cuestas 2008), satisfaction, and repurchase intention (Agag et al 2016). However, these studies do not help to understand how ethical perceptions relate to consumer participation and their value co-creation intentions on SEPs.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in an electronic market environment, buyers and suppliers come together in a market space and exchange information related to price, product specifications, terms of trade, and a dynamic price-making mechanism facilitates transactions between the firms (Kaplan and Sawhney 2000). Palmatier et al (2006), Morgan and Hunt (1994), and Agag and ElMasry (2016b) and Agag et al (2016) used communication as an antecedent of trust and commitment. One factor that distinguishes firms that merely possess information from those that use information is the level of trust users have in producers of information Lancastre and Lages (2006).…”
Section: Communication and Relationship Qualitymentioning
confidence: 99%
“…Online shoppers are most concerned about the privacy and security of their personal and financial information (Devaraj et al, 2002;Liu & Arnett, 2000;Wolfinbarger & Gilly, 2003). The security and privacy dimension of e-retail service quality includes the security of customer credit/debit card details and protection of personal information that a customer needs to share to complete his/her online purchasing (Agag, El-Masry, Alharbi, & Ahmed Almamy, 2016;Wolfinbarger & Gilly, 2003). Security and privacy are regarded as one of the key criteria on which a consumer assesses the trustworthiness of an online organisation (Aiken & Bousch, 2006;Hoffman, Novak, & Peralta, 1999).…”
Section: Electronic Service Qualitymentioning
confidence: 99%